Teaching Tajweed Science and Instilling Manners Through the Al-Quran Study Program for Early Childhood in Bongas Village - Siti Anisah (Konsultan Jurnal Ilmiah Indonesia, 2024)
The purpose of this program: to motivate children to learn, Increase understanding in early childhood about the procedures for reading the Qur'an properly and correctly according to the rules that have been determined, make it easier for children to recite the Qur'an. There are several benefits to be gained from studying Tajweed, namely it can be practiced when reciting the Qur'an, sounding the recitation of the Qur'an beautifully and correctly. The method used in teaching Tajweed is by using the lecture method, explaining the meaning of Tajweed, the rules of reading it and how to read it. When the delivery is complete, it continues with a question and answer session, which is expected that students can repeat the material that has been delivered. The results of this Community Service are to help children understand the meaning of Tajweed by practicing little by little, although not all children can understand it. Learning Tajweed takes a lot of time in teaching, so the program that is carried out has not fully made all children understand Tajweed.